Seasonal Occurrence and Distribution on Grapevine Roots of Eurhizococcus brasiliensis (Wille) (Hemiptera: Margarodidae) in Brazil - Schmidt, F.S.; Leite, L.G.; de Klerk, C.A.; Canesin, A.; Marraschi, R.; Ballone, P. (South African Journal of Enology and Viticulture, 2016)
The ground pearl, Eurhizococcus brasiliensis (Wille) (Hemiptera: Margarodidae), is the most important grapevine pest in Brazil. Its seasonal occurrence and distribution on the roots of the different development stages were determined to allow better monitoring of this insect and better targeting of its vulnerable life stages. Yellow cysts (after the first nymphal moult) showed the lowest density in October, followed by a gradual increase towards August. White cysts (cysts with enclosed pre-pupal males or females) occurred from August to December, with a peak in November. Mobile females (adult females emerging from the white cysts) were found from August to December, with a peak in August. Parthenogenetic females that remain in the ruptured white cysts for egg laying were present from August to April, with a peak in November. Mobile nymphs (first instar) were also found from August to April, with a peak in December. Yellow cysts were most abundant at depths of 0 to 25 cm. The horizontal survey showed that cysts occurred mostly on the trunk below the ground (trunk of the rootstock), and that almost all occurred in an area of 20 cm width around the trunk. These results provide important information for better monitoring of this pest and to develop better methods for and timing of chemical control.